2016
DOI: 10.4314/aas.v13i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Scaphoid Nutrient Foramina

Abstract: Introduction: Avascular necrosis (AVN) is a frequent complication of scaphoid fractures especially those involving the proximal segment of the bone. This has been attributed to its precarious blood supply which is further compromised by the fracture and surgery. Knowledge of the distribution of scaphoid nutrient foramina, which show variation across populations, is thus important in estimating the risk of vascular damage during surgical approaches and hence the likelihood of AVN. It may also be useful in deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Number of vascular foramina is more on the dorsal surface (1 -24) than volar surface (3 -7). This finding is consistent with Dubey et al [4] and Owira et al [8] who reported that dorsal to volar ratio is 4:1 and 4.23:1 respectively. In the present study it is 3.42:1.…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…Number of vascular foramina is more on the dorsal surface (1 -24) than volar surface (3 -7). This finding is consistent with Dubey et al [4] and Owira et al [8] who reported that dorsal to volar ratio is 4:1 and 4.23:1 respectively. In the present study it is 3.42:1.…”
Section: Methodssupporting
confidence: 83%
“…There is no foramen proximal to the mid waist in 6% scaphoid bones as reported by Dubey et al [4], in 13% scaphoids as observed by Obletz [3] and in 3% bones in the present study. Owira [8] observed type I (no foramina) scaphoids in 54% cases. It can be stated that in such cases when there is a fracture of waist, there will be diminished blood supply to the proximal fragment leading to nonunion or avascular necrosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation